The Guman of Dumalinao. [anthology].
A traditional "buklog" or feast is held to celebrate the union of the two kingdoms. "Guman" is an epic of the Suban-on tribe who inhabit the highlands of Northwestern Mindanao, in the territory that is now partitioned among the three provinces of Misamis Occidental, Zamboanga del Norte, and Zamboanga del Sur.
Found in: Philippine Folk Literature: The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.